Using neurostimulation to understand the impact of pre-morbid individual differences on post-lesion outcomes - Woollams, Anna M. (Proc Natl Acad Sci U S A, 2017)
Neuropsychological data have proven invaluable in advancing our understanding of higher cognition. The interpretation of such data is, however, complicated by the fact that post-lesion behavioral abnormalities could reflect pre-morbid individual differences in the cognitive domain of interest. Here we exploited the virtual lesion methodology offered by transcranial magnetic stimulation (TMS) to explore the impact of pre-morbid individual differences on post-lesion performance. We applied this approach to the domain of reading, a crucial ability in which there are known to be considerable individual differences in the normal population. As predicted by neuropsychological studies of surface dyslexia in semantic dementia and the connectionist triangle model of reading, previous empirical work has shown that healthy participants vary in their reliance on meaning for reading words with atypical correspondences between spelling and sound. We therefore selected participants who varied along this dimension and applied a virtual lesion to the left anterior temporal lobe. As expected, we observed a significant three-way interaction between “pre-morbid” reading status, stimulation, and word type, such that TMS increased the disadvantage for spelling–sound atypical words more for the individuals with stronger semantic reliance. This successful test-case study provides an approach to understanding the impact of pre-morbid individual variation on post-lesion outcomes that could be fruitfully applied to a variety of cognitive domains.